The Effect of Gastric Electrical Stimulation on Small Bowel Motility in Patients With Gastroparesis and Concomitant Pancreatic and Small Bowel Dysfunction: From Animal Model to Human Application. Issue 6 (7th December 2018) - McKenzie, Patrick; Stocker, Abigail; Du, Peng; Lahr, Christopher; Cheng, Leo K.; McElmurray, Lindsay; Kedar, Archana; Boatright, Benjamin; Hassan, Hamza; Hughes, Michael; Omer, Endashaw; Bhandari, Bikash; et al.
Abstract : Background/Aims: Patients with gastroparesis often have biliary/pancreatic and small bowel symptoms but the effects of gastric electrical stimulation on small bowel electrical activity of the mid‐gut have not been studied. Animal model aim: Establish gastric and upper small bowel/biliary slow wave activity relationships with electrical stimulation. Human study aim: Demonstrate improvement in symptoms associated with proximal small bowel dysmotility in gastric stimulated patients. Materials and Methods: Animal model: In vivo evoked responses of duodenal and Sphincter of Oddi measures recorded during gastric electrical stimulation in a nonsurvival swine model ( N = 3). High‐resolution electrical slow wave mapping of frequency, amplitude, and their ratio, for duodenal and Sphincter of Oddi electrical activity were recorded. Human study: Patients ( N = 8) underwent temporary gastric stimulation with small bowel electrodes. Subjective and objective data was collected before and after temporary gastric stimulation. Symptom scores, gastric emptying times, and mucosal electrograms via low‐resolution mapping were recorded. Results: Animal gastric stimulation resulted in some changes in electrical activity parameters, especially with the highest energies delivered but the changes were not statistically significant. Human study revealed improvement in symptom and illness severity scores, and changes in small bowel mucosal slow wave activity. Conclusions: Gastric electrical stimulation in an animal model seems to show nonsignificant effects small bowel slow wave activity and myoelectric signaling, suggesting the existence of intrinsic neural connections. Human data shows more significance, with possible potential for therapeutic use of electrical stimulation in patients with gastroparesis and pancreato‐biliary and small bowel symptoms of the mid‐gut. This study was limited by the nonsurvival pig model, small sample size, and open label human study.